USING CROWDSOURCING FOR PROJECT MANAGEMENT - Alimuddin Alimuddin (Universitas Muhammadiyah Sorong, 2020)
Crowdsourcing is coined first by Jeff Howe and become more popular in recent years. It is concept of outsourcing in the crowd. Crowdsourcing can be useful to project managers when they need to perform tasks with low budget, massive participants, multi-disciplinary, expert or non-experts. Using 10 rules from Howe will help a project manager manage the crowd and achieve their project objective. By addressing some questions such as why should a project manager use crowdsourcing? What the benefits and risks of crowdsourcing. This articles explain the contribution of crowdsourcing in project and change management